The Routledge Handbook of Chinese Studies - Shei, Chris; Wei, Weixiao (Taylor & Francis, 2021)
Chinese, language learning, foreign policy, Chinese political system, domestic governance, international relations, Chinese culture, Chinese literature, Chinese history, Chinese sociology, Chinese opposition, Chinese activism, Chinese people, Chinese society, Chinese studies